1991
DOI: 10.1111/j.1346-8138.1991.tb03148.x
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrochlorobenzene Treatment of Verrucae Plana

Abstract: In a purely clinical, unbiased study, 50 patients with verrucae plana were treated with dinitrochlorobenzene for 1-24 weeks, keeping half the lesions as controls. The results were statistically insignificant when the treated patients were compared to the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…The largest prospective placebo‐controlled half‐body study was a series of 50 patients with plane warts treated with DNCB on one half and acetone on the other 138 . Twenty‐seven (54%) of patients cleared on the DNCB‐treated side and 19 (38%) on the acetone‐treated side.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest prospective placebo‐controlled half‐body study was a series of 50 patients with plane warts treated with DNCB on one half and acetone on the other 138 . Twenty‐seven (54%) of patients cleared on the DNCB‐treated side and 19 (38%) on the acetone‐treated side.…”
Section: Resultsmentioning
confidence: 99%
“…The largest prospective placebo-controlled half-body study was a series of 50 patients with plane warts treated with DNCB on one half and acetone on the other. 138 Twenty-seven (54%) of patients cleared on the DNCB-treated side and 19 (38%) on the acetonetreated side. Eight of the DNCB-treated sides relapsed during a 6-month follow-up period, resulting in a longterm clearance rate of 38% on either side, showing no advantage of DNCB treatment over placebo.…”
Section: Wartsmentioning
confidence: 98%
“…4,5 Other treatments reported to be effective are infrared coagulation, 6 intralesional injection of bleomycin, 7 natural a-interferon 8 topically applied 5-fluorouracil 9 and application of immunosentisizing dinitrochlorbenzene. 10 However, in spite of all of these therapeutic modalities some warts remain resistant to therapy, and recalcitrant warts are a matter of great concern for the patient and the dermatologist. Bunney et al reported in 1976 5 that 70% of common warts, 80% of simple plantar warts and 50% of mosaic plantar warts were cured by simple methods, but that a subgroup of patients with resistant warts are left.…”
Section: Introductionmentioning
confidence: 99%
“…Antimitotic therapy is achieved by podophyllin/podophyllotoxin, bleomycin, and retinoids [1,6,8,9,14,16]. Immune stimulation can be initiated with dinitrochlorobenzene, squarid acid dibutylester, diphencyprone and cimetidine [2,12,21,22,23,30].…”
Section: Discussionmentioning
confidence: 99%
“…There is no single treatment that is 100% effective, and different types of therapy may be combined. The appropriate treatment option depends on a variety of factors (including the age of the patient, location of the lesion, past treatment, etc) and includes a variety of acids, podophyllin, podophyllotoxin, chemotherapeutic agents, retinoids, topical sensitizers, a spectrum of surgical techniques, and cryotherapy [1,2,3,6,7,8,9,11,12,13,14,15,16,21,22,23,24,25,26,28,29,30].…”
Section: Introductionmentioning
confidence: 99%